O lugar do projeto de formação profissional diante da mercantilização do ensino na região ABEPSS Centro-Oeste - Ferreira, Regiane Carla Mayer (2020)
Taking as a starting point the study of the mercantilization of higher education in Brazil and its implications for the professional training project, this dissertation proposes as a general objective to analyze the dynamics of the commodification of undergraduate courses in Social Work, in the ABEPSS Midwest region, from the data made available by the e-MEC Register, considering the date of creation of new courses, the type of IES (public or private) and the teaching modality (in person or distance education). In order to achieve this objective, the questions were deepened based on the following specific objectives: a) to analyze the expansion of the commercialization of undergraduate courses in Social Work in the ABEPSS Midwest region, considering the on-site and distance education teaching modality; b) identify whether the creation of undergraduate courses in Social Work in the ABEPSS Midwest region follows the same accelerated pace of deepening the commercialization of higher education registered at the national level. Developed from the perspective of Marxist social theory, the methodological path proposed for this work combines elements of the quantitative and qualitative approaches, with an emphasis on the second. This study has an exploratory character articulated with the appropriation of elements from bibliographic and documentary research. As a result, the data reveal that the commercialization of professional training in Social Work in the Regional Center-West of ABEPSS is a reality enhanced by the accelerated expansion of private higher education, in particular, distance learning, the well-known Distance Education, accompanying the same accelerated pace registered at the national level. It is a logic that will play a strategic role in the massification of the social and educational contradictions experienced in the current context, putting in perspective the need for a new social and school organization, in addition to capital, this in terms of Mészáros 2008, since this it cannot deliver on the promised promises.